BIM-based LCA assessment of seismic strengthening solutions for reinforced concrete precast industrial buildings - Raposo, Cátia (2019)
Construction sector contracts have relevant socioeconomic importance in contrast with its high environmental impact due to the intensive consumption of natural and energy resources throughout the buildings’ service life. Thus, this sector has been object of actions aiming the promotion of low carbon construction and refurbishment given its potential to reduce emissions of greenhouse gases by applying more sustainable materials and techniques. With the development of the building information modeling (BIM) methodology, it is possible to develop the different project specialities in an integrated and collaborative platform since its initial phase, also facilitating the integration of life cycle assessment (LCA). The present work aims to evaluate and compare the environmental impacts of prefabricated concrete elements of new construction and solutions of seismic reinforcement of these elements in an existing building, as well as their costs, through LCA methodology and life cycle cost (LCC). For this purpose, the BIM model of an industrial building with a prefabricated concrete structure was developed and the respective LCA was achieved. It was considered the model of a similar building with 30 years of existence, whose structural calculation not considered the correct strengthening to face seismic actions. The respective seismic reinforcement solution was analyzed, and the corresponding LCA was accomplished. For each case, the LCC was calculated. The analysis of the two buildings highlighted the importance of rehabilitation in the construction sector, since the environmental impacts and the associated costs are reduced when compared to the construction of a new building.